Reactive and proactive aggression in children with and without ADHD and negative emotional lability. Issue 1 (22nd August 2019) - Slaughter, Kelly E.; Leaberry, Kirsten D.; Fogleman, Nicholas D.; Rosen, Paul J.
Abstract: Children with attention‐deficit/hyperactivity disorder (ADHD) exhibit marked difficulty with frequent and intense shifts in negative or positive emotions, referred to as emotional lability. This study examines the relationships between negative emotional lability (NEL), ADHD, and reactive and proactive aggression. A community sample of 96 children (53 with ADHD, 43 control) ages 8–12 and their parents completed a baseline session include a diagnostic structured interview and the Reactive–Proactive Aggression Questionnaire (RPAQ). Parents then rated their child's NEL using the Positive and Negative Affect Scale as part of an Ecological Momentary Assessment protocol 3 times a day for 28 days. Seventy‐three participants (37 with ADHD, 36 control) completed the RPAQ at follow‐up. Hierarchical regression analyses indicated that NEL significantly and independently estimates reactive aggression at baseline and follow‐up, regardless of ADHD status. NEL and ADHD status significantly estimates concurrent proactive aggression, but not at follow‐up. Results of this study suggest that NEL accounts for a significant amount of the variability in reactive aggression, a common difficulty in children with ADHD. Further, individuals that are reportedly emotionally labile become more reactively aggressive over time. Both ADHD diagnostic and NEL are predictors of proactive aggression at baseline, although no interaction occurred.